CHANGES IN QUALITY OF LIFE AFTER SHORT AND LONG TERM FOLLOW-UP OF ROUX-EN-Y GASTRIC BYPASS FOR MORBID OBESITY - LAURINO NETO,Rafael M. (2013)
Context It is unclear whether health-related quality of life (HRQL) is sustained in a long-term follow-up of morbidly obese patients who underwent Roux-en-Y gastric bypass (RYGB). Objective This study aims to analyze the HRQL changes following RYGB in short and long-term follow-up. Methods We compared the health-related quality of life among three separate patient groups, using the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). Group A - 50 preoperative morbidly obese patients; Group B - 50 RYGB patients 1-2 years post-surgery; Group C - 50 RYGB patients more than 7 years post-surgery. Results The groups were similar for gender, age and body mass index before surgery. We observed that physical functioning, social function, emotional role functioning and mental health scales did not vary between the three groups. The physical role functioning scale was unchanged in the short-term and decreased compared to the preoperative scale in the long-term follow-up. Bodily pain improved after the operation but returned to the initial level after 7 years. The vitality and general health perceptions improved after the operation and maintained these results after 7 years compared with the preoperative perceptions. Conclusions RYGB improved health-related quality of life in three SF-36 domains (bodily pain, general health perceptions and vitality) in the short-term and two SF-36 domains (general health perceptions and vitality) in the long-term.